Asthma control test administered by web-based text messaging (short message service-SMS): Is it comparable with paper form? - Uysal, Mehmet Atilla; Mungan, Dilsad; Yorgancioglu, Arzu; Yildiz, Fusun; Akgun, Metin; Gemicioglu, Bilun; Turktas, Haluk (European Respiratory Soc Journals Ltd, 2012)
[Abstract Not Available]
Keywords: Asthma - management; Telemedicine; Quality of life